Utilidad de la gasometría para la valoración clínica del paciente con Covid-19 - Farinango Romero, Katherin Lizeth, Estrella Pucha Jessenia Katerine, Gisnella Cedeño Cajas (2022)
ABSTRACT: The objective of this research work was to develop a bibliographic review about the usefulness of blood gases in the clinical assessment of patients with Covid-19. The methodology had a non-experimental, descriptive cross-sectional, bibliographic design. The population were 120 bibliographies investigated, the sample consisted of 55 articles cited which allowed to show that by means of the valuation of the gasometry, alterations can be identified, when the pH and HCO3 are low, a metabolic acidosis develops; when pH and HCO3 increase, metabolic alkalosis occurs; when the pH decreases and the CO2 increases, respiratory acidosis develops; when the pH increases and CO2 decreases, a respiratory alkalosis occurs; when O2 saturation values are less than 90%, respiratory failure is recorded. In the same way, it was possible to identify that it is the male population who have developed more complications from Covid-19, because through the clinical assessment of arterial blood gases, their indices have been found to be altered, evidencing the need for mechanical ventilation; likewise, it has been known that boys and girls are less likely to suffer serious consequences, because when performing the gasometric examination, their indices have not been altered. It is concluded that the clinical assessment of blood gases in Covid-19 patients is of great importance because it allows detecting respiratory problems, respiratory alkalosis, hypoxia and hypoxemia, and pulmonary diseases such as cystic fibrosis, pneumonia. The same ones that can be treated with said valuation. Keywords: Gasometry - Covid-19 - Pulmonary conditions - Hypoxia - Mechanical Ventilation - Oxygenation.